Evolusi dan Pola Kejahatan dalam Sistem Perbankan: Dari Penipuan Tradisional hingga Kejahatan Siber - Efendi, Mohamad Nur; Adinugroho, Mukhtar; Khomairoh, Selvina (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2025)
This study examines evolving crime patterns in the banking sector, highlighting the shift from conventional fraud to sophisticated cybercrimes such as phishing, ransomware, and data breaches. Digitalization and financial innovation have had a profound impact on criminal strategies, exposing vulnerabilities in digital systems and creating new security challenges for banks. Utilising a literature review method, the research explores the nexus between cybercrime and money laundering (TPPU) as well as terrorism financing (TPPT). In these contexts, cyberattacks frequently facilitate the execution of untraceable international transactions. The study recommends the adoption of technologies such as AI-based anomaly detection, the tightening of cybersecurity regulations, and the improvement of cyber awareness among employees and customers. Furthermore, it emphasises the enhancement of the supervisory role of Indonesia's Financial Transaction Reports and Analysis Center (PPATK) in monitoring digital financial flows and the promotion of international information sharing. Cross-sector collaboration among financial institutions, regulators, and technology providers is deemed crucial to strengthening the global financial system's defences. These measures are intended to enhance Indonesia's Anti-Money Laundering and Countering the Financing of Terrorism (APU PPT) framework in response to the growing risks of the digital era.